Modification of polymer electrolyte membranes for DMFCs using Pd films formed by sputtering - Yoon, SR; Hwang, GH; Cho, WI; Oh, IH; Hong, SA; Ha, HY (ELSEVIER SCIENCE BV, 2002)
Composite polymer electrolyte membranes were fabricated by depositing Pd films on the surface of Nafion(TM) membranes by sputtering, and the modified membranes were investigated for their morphologies, methanol permeabilities, protonic conductivities and performances for direct methanol fuel cells (DMFCs). The Pd film acted as a barrier to methanol crossover, but at the same time it also reduced proton conductivity. Though both the methanol permeability and the protonic conductivity through the modified membranes decreased with increasing g Pd thickness, the cell performances were almost independent of the Pd thickness. The effects of methanol concentration on the protonic conductivity and the cell performance were also investigated. And, the role of Pd Elms in DMFCs is discussed in some detail. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: METHANOL FUEL-CELL; NAFION/SILICA HYBRID MEMBRANE; PROTON-EXCHANGE MEMBRANES; CROSSOVER